1996
DOI: 10.1021/ja961733f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Aromatic Stacking Affinities in the Context of Duplex DNA

Abstract: Noncovalent interactions between aromatic molecules are widely believed to be important contributing factors in the stabilization of organized structure in biological macromolecules. 1,2 Among the most significant aromatic-aromatic interactions are those found in helical nucleic acid structures. Since the identity of the nearest neighbors to a given base pair is the best single predictor of thermodynamics in DNA duplexes, 3 it is clear that aromatic π-π interactions are crucial to the stabilization of these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
231
3
9

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 261 publications
(262 citation statements)
references
References 28 publications
19
231
3
9
Order By: Relevance
“…The solvation energy of the dangling base will also drive the stacking equilibrium toward the stacked form, thus directly affecting the dynamics of the dangling end. This is in agreement with the recently published results that have shown that the higher the hydrophobicity and polarizability (a m ) of the dangling end, the more stability it provides to the duplex when attached as dangling end (37,42), even if the stacking areas and geometries are presumably constant. We also propose that the reason that further stabilization is gained when additional dangling bases are added to an overhang sequence is that the additional dangling nucleotides reduce the dynamics of the innermost dangling base by nearest-neighbor intrastrand stacking interactions.…”
Section: Dangling-end Stabilization and Stacking Geometrysupporting
confidence: 93%
“…The solvation energy of the dangling base will also drive the stacking equilibrium toward the stacked form, thus directly affecting the dynamics of the dangling end. This is in agreement with the recently published results that have shown that the higher the hydrophobicity and polarizability (a m ) of the dangling end, the more stability it provides to the duplex when attached as dangling end (37,42), even if the stacking areas and geometries are presumably constant. We also propose that the reason that further stabilization is gained when additional dangling bases are added to an overhang sequence is that the additional dangling nucleotides reduce the dynamics of the innermost dangling base by nearest-neighbor intrastrand stacking interactions.…”
Section: Dangling-end Stabilization and Stacking Geometrysupporting
confidence: 93%
“…In the last two decades π-stacking interactions between aromatic systems have been extensively studied. This interaction has been proposed to be a pivotal assembly force in many important supramolecular systems including various protein and enzyme substrates, 53 nucleic acids, 54 and molecular catalysts. 55 A deeper understanding of the nature of the interaction is the key step for developing the synthesis of controlled nanoscale structures.…”
Section: π -π Interactionsmentioning
confidence: 99%
“…A previous preliminary study reported dangling end measurements for a few of these analogues but did not include all four natural bases, did not include structural data, and did not correlate the results with physical properties or solvent effects. 50 …”
Section: Structure and Design Aspects Of The Nucleosides Studiedmentioning
confidence: 99%